2002
DOI: 10.1103/physrevb.65.212103
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-induced dark-to-bright transition inLu2O3:Ce

Abstract: Application of pressure to the nonemitting system Lu 2 O 3 :Ce 3ϩ leads to the generation of luminescence in the visible. The luminescence is assigned to the 5d→4 f transition of Ce 3ϩ , and is attributed to a pressureinduced electronic crossover of the excited 5d state of Ce 3ϩ and the conduction-band edge of Lu 2 O 3 . The results yield insight into the emission efficiency of 5d→4 f transitions, and provide a foundation for advancing new phosphors and tunable laser materials in the visible and ultraviolet ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…Auto-ionization of the excited electron, followed by a nonradiative decay to the 4f ground state, was understood to be the quenching mechanism [3], quite commonly accepted in explaining the properties of various systems [4]. A good experimental demonstration of the validity of this hypothesis comes from a set of recent high-pressure experiments [5,6]. Dark-to-bright transition due to hydrostatic pressure is shown to occur in a closely related material Lu 2 O 3 :Ce at about 70 kbar.…”
mentioning
confidence: 98%
“…Auto-ionization of the excited electron, followed by a nonradiative decay to the 4f ground state, was understood to be the quenching mechanism [3], quite commonly accepted in explaining the properties of various systems [4]. A good experimental demonstration of the validity of this hypothesis comes from a set of recent high-pressure experiments [5,6]. Dark-to-bright transition due to hydrostatic pressure is shown to occur in a closely related material Lu 2 O 3 :Ce at about 70 kbar.…”
mentioning
confidence: 98%
“…luminescence from the lowest 5d state will be observed. Also in analogy to LSO, the pressure induced lowest 5d state in the oxide is subject to quenching through thermal activation back into the conduction band [15].…”
Section: Localization/delocalizationmentioning
confidence: 99%
“…18 Moreover, Ce 3+ gives no photoluminescence emission in yttria matrix, because the 5d-4f transition of Ce 3+ is not enveloped in the bandgap of yttria. 19,20 Therefore, compared to YAG, AlON, and MgAl 2 O 4 , yttria is a better host material of Ce ions for UV absorption. In this study, the authors demonstrated the fabrication of highly transparent cerium-doped yttria ceramics by a pressureless sintering route.…”
Section: Introductionmentioning
confidence: 99%
“…briefly reported the fabrication and optical transparency of a Ce‐doped transparent yttria ceramic specimen, which showed an absorption edge at ∼370 nm 18 . Moreover, Ce 3+ gives no photoluminescence emission in yttria matrix, because the 5d–4f transition of Ce 3+ is not enveloped in the bandgap of yttria 19,20 . Therefore, compared to YAG, AlON, and MgAl 2 O 4 , yttria is a better host material of Ce ions for UV absorption.…”
Section: Introductionmentioning
confidence: 99%